The structure of German trade with Africa - Hans Wallner (Intereconomics, 1972)
The structure of Germany's trade with Africa differs substantially from the general pattern of its foreign trade relations. But there is a further pecullarity in this trade. Each of the African countries concerned has a very specific importance as a trading partner. The following article reviews the characteristic features of African-German trade relations.
Keywords: 330; Germany